Customer Preference in Starbucks SM Fairview Branch: Basis for Improved Customer Satisfaction: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Starbuck is the most leading coffee houses around the globe most especially here in Manila.Everyday, Filipinos start their day with a cup of coffee, it is like a traditional way of makingtheir day lively as they are woken by every zip of coffee. Starbucks has been popular frombefore till now, it's because they have provided the best coffee and places for its customerswhereas they are known for being a high-class coffee house and it is because of their coffeespecialty and luxury vibrant store. Coffee’s preferences evolve from a simple way of brewingcoffee to a complicated new version, same as for the ambiance of the place where they haveinnovated but still customers' needs are complex. So, in this study, the researchers havecome up with the ideas to allocate the possible existing unsatisfied customer and to collect abasis for customer satisfaction.As for the results, the researchers found out that most customers of Starbucks at SMFairview Branch are 18-25 years old, female, a student and single, and they are satisfiedwith the taste, service, ambiance, and presentation which defer to the price where mostanswered that they are not satisfied. The most encountered problem by customers is thatthe mall time opening and closing is too early, making it difficult for them to drink coffee inthe morning.At the end of the research, the researchers found out that based on the results, Starbuckshas always had a long line up at the counter, and some products are way too pricey andmost of the respondents say that they are struggling to open and close it. Therefore, theresearchers have come up with the idea to create an action steps or action plan torecommend improved customer satisfaction at Starbucks SM Fairview branch. Theresearchers plan to apply an online ordering system to lessen the line at the counter, collectdata for other bases and information, and post a card outside or online for customersacceptance.Keywords:
Keywords: Business Administration